MAKING VOCABULARY WHEEL GAME FOR JUNIOR HIGH SCHOOL STUDENTS - Nurul Izati; boni Saputra (INOVISH JOURNAL, 2016)
Abstract : Vocabulary is an essential part of English learning. Mastering English words help students acquire the language. However, many teachers still use traditional ways in teaching Vocabulary. They only refer to text books and ask students to remember words without using any media. Lack of teaching media makes students feel boring and not interested in learning English. It is also hard for students to understand the language. The research question was “Is there a Wheel Game to learn Vocabulary for junior high school Students? The objective of this study was to make Vocabulary Wheel Game for Junior high school students. The method used in this study was descriptive research. It explained the problem qualitatively to uncover solutions. This product is an adaptation of wheel of fortune game. Its colorful design and a lot of pictures can attract students to learn vocabulary in a fun way. As mentioned above, the model of wheel already exists. However, the whole model, wheel, color, and the pictures were designed using tools from several applications and were made of wooden and paper material. The wheel in this game has sectors and each sector uses 26 alphabets. This game uses one type of card, called penalty card, which contain a lot of interesting pictures. The cards were printed in the photo papers.                             Keywords:   English, Vocabulary Wheel Game, Teaching Medium.